Impact of visual and auditory deprivation on speech perception and production in adults. - Turgeon, Christine; Trudeau-Fisette, Paméla; Lepore, Franco; Lippé, Sarah; Ménard, Lucie (Clinical Linguistics & Phonetics, 2020)
Speech perception relies on auditory and visual cues and there are strong links between speech perception and production. We aimed to evaluate the role of auditory and visual modalities on speech perception and production in adults with impaired hearing or sight versus those with normal hearing and sight. We examined speech perception and production of three isolated vowels (/i/, /y/, /u/), which were selected based on their different auditory and visual perceptual saliencies, in 12 deaf adults who used one or two cochlear implants (CIs), 14 congenitally blind adults, and 16 adults with normal sight and hearing. The results showed that the deaf adults who used a CI had worse vowel identification and discrimination perception and they also produced vowels that were less typical or precise than other participants. They had different tongue positions in speech production, which possibly partly explains the poorer quality of their spoken vowels. Blind individuals had larger lip openings and smaller lip protrusions for the rounded vowel and unrounded vowels, compared to the other participants, but they still produced vowels that were similar to those produced by the adults with normal sight and hearing. In summary, the deaf adults, even though they used CIs, had greater difficulty in producing accurate vowel targets than the blind adults, whereas the blind adults were still able to produce accurate vowel targets, even though they used different articulatory strategies.